Features of forced execution of agrarian notes - Avtorgov, A. M. (Аналітично-порівняльне правознавство, 2025)
The article is devoted to the analysis of legal regulation and practical aspects of enforcing agrarian notes as a new financial instrument introduced to support the financing of agricultural production. An agrarian note is defined as a non-issuable security that ensures the debtor’s unconditional obligation to deliver agricultural products or pay monetary funds to the creditor in accordance with the terms specified in the document. The article provides a detailed examination of the legal nature of agrarian notes, their differences from agrarian receipts, and outlines the advantages of implementing this instrument into Ukraine’s financial system. Particular attention is paid to analyzing the novelties introduced by the Law of Ukraine «On Agrarian Notes», which comes into effect on January 1, 2025, and their impact on ensuring effective enforcement proceedings. The mechanisms of compulsory enforcement of agrarian notes are explored, including execution based on court decisions, decisions of international commercial arbitration, arbitral tribunals, or special extracts from the Agrarian Notes Register. The role of collateral as a primary means of securing obligations is highlighted, including innovative approaches such as the use of livestock or animal-derived products as collateral. Issues related to the enforcement of claims on agricultural products as the subject of collateral are analyzed, alongside the potential for using digital technologies to enhance transparency and efficiency in these procedures. The article also evaluates regulatory restrictions concerning the impossibility of enforcing claims on agricultural land owned by the debtor. A special emphasis is placed on examining the differences between financial and commodity agrarian notes, focusing on their enforcement procedures and legal implications for the parties involved. Problematic aspects of executing notarial writs on grain storage facilities and other contentious issues arising in the implementation of this instrument are investigated. The author concludes that further legislative improvements are necessary to enhance the effectiveness of agrarian note enforcement and ensure consistency in the legal regulation of this instrument with other normative acts governing enforcement proceedings. The proposals outlined in the article aim to create favorable conditions for attracting investments in agriculture and developing innovative financial mechanisms.